Karakteristik Selai Albedo Kulit Durian (Durio zibethinus) dengan Aplikasi Penyaringan dan Penambahan Pektin - Sugito, Sugito; Rafiqah, Thara N; Syafutri, Merynda I; Syaiful, Friska; Rosidah, Umi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Sugito, S., Rafiqah, T. N., Syafutri, M. I., Syaiful, F., & Rosidah, U. (2024). characteristics of durian skin albedo jam (Durio Zibethinus) with application of filtering and pectin addition. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 281–292). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This research aimed to determine the effect of filtration and pectin concentration on the physical, chemical, and sensory characteristics of durian skin albedo jam. This research used a Factorial Completely Randomized Design with two treatment factors. The first treatment (factor A) was filtration which consisted of two treatment levels (filtration and without filtration), the second treatment (factor B) was pectin concentration which consisted of four treatment levels (0%, 0,5%, 1%, 1,5%). Each treatment was repeated three times. Parameters observed in this research included physical characteristics (color L* a* b*, viscosity, and spreadability), chemical characteristics (water content, total dissolved solids, pH, and crude fiber), and sensory characteristics (texture, taste, and color). The results showed that the filtration treatment had a significant effect on lightness, yellowness, viscosity, spreadability, water content, and crude fiber, while the pectin concentration had significant effect on lightness, viscosity, spreadability, water content, pH, total dissolved solids, and crude fiber. The interaction between of the two factors had significant effect on viscosity and crude fiber of durian skin albedo jam. The best treatment in this study was the A1B4 (filtering and pectin 1,5%) with a lightness (69.94), redness (4.65), yellowness (10.67), viscosity (316.67 dPa.s), spreadability (25.50 cm), water content (33.48%), pH (3.87), crude fiber (2.53%), sensory texture (2.88), taste (2.96), and color (2.72).